REALIZATION OF THE PRINCIPALS OF A QUALITY MANAGEMENT ON THE BASIS OF THE USE OF THE APPLICATION SOFTWARE - Nikolai D. Koryagin (Статистика и экономика)
The article presents a systematic analysis of the problems solved by different classes of modern application software for implementation of the principles of a total quality management.